A comparison study on the mechanical properties of composites based on kenaf and pineapple leaf fibres - Dhar Malingam, Sivakumar; Ng, Lin Feng; Selamat, Mohd Zulkefli; Mustafa, Zaleha; Bapokutty, Omar (Springer, 2020)
The arising trend of using natural fibres in the composite materials has stimulated the continuous exploration of their mechanical properties. The positive environmental behaviours of natural fibres are the driving factor that allows them to gain their wide acceptance in industries. However, the mechanical behaviour of natural fibre-based composites is still not fully explored. In this research study, the mechanical properties of composite materials with different types of natural fibre and various fibre compositions were investigated. The polypropylene-based composite materials were fabricated through hot press compression moulding method using a hydraulic hot press machine. The composites were then subjected to mechanical tests to study the tensile, flexural and impact properties of such materials. The results demonstrated that the tensile strength and flexural strength of pineapple leaf fibre (PALF)-based composites were 7.83% and 54.23% higher than kenaf-based composites at a fibre content of 30 wt%. Moreover, the impact strength of PALF-reinforced composites was 3.08% and 5.56% higher than kenaf fibre-reinforced composites in the flatwise and edgewise impact orientations. Overall, composites with 30 wt% evidenced the top most mechanical properties irrespective of types of plant fibre.